Association between match activity variables, measures of fatigue and neuromuscular performance capacity following elite competitive soccer matches - Varley, I.; Lewin, R.; Needham, R.; Thorpe, R. T.; Burbeary, R. (Journal of Human Kinetics, 2017)
The aim of the study was to assess the relationships between match activity variables, subsequent fatigue and neuromuscular performance capacity in elite soccer players. Subjects (n = 10) were professional soccer players participating in the English Championships. Match activity variables and markers of fatigue status were measured before and following two matches. Creatine kinase (CK) and muscle soreness were measured at baseline, immediately following, as well as 40 and 64 h post-match. Countermovement jump performance and perceived ratings of wellness were measured at baseline, then 40 and 64 h post-match. Relationships were shown between CK and the total number of accelerations and decelerations immediately (r = 0.63; large), 40 h (r = 0.45; moderate) and 64 h post-match (r = 0.35; moderate) (p < 0.05). Relationships between CK and total sprint distance (r = 0.39; moderate) and the number of sprints (r = 0.35; moderate) 40 h post-match (p < 0.05) were observed. Furthermore, relationships were shown between the perceived rating of wellness and number of accelerations 40 (r = 0.52; large) and 64 h (r = 0.40; moderate) post-match, sprint distance 40 h post-match (r = 0.40; moderate) and the total number of sprints 40 h post-match (r = 0.51; large) (p < 0.05). The quantification of match activity variables, particularly the total number of accelerations and decelerations and the number of sprints, provides insights into the fatigue status in elite soccer players 40 and 64 h post-match.